KUALITAS SISTEM INFORMASI APLIKASI PENDIDIKAN (SIAP) DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA SERANG - Sopyan Syuri; Riswanda 1; Yearry Panji Stainto (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
Progress in government technology and information can be seen from administrative services that are computer based. The implementation of e-Governance is one form of business carried out by the City Government of Serang, in carrying out its government activities more effectively and efficiently. Principles that provide support, through design, data flow and the final process of implementation are then made and developed Education Application Information Systems (SIAP). The method used in this research is quantitative research methods. Data collection is done by questionnaire and interview techniques while the sampling technique uses accidental sampling. This means that the determination of the sample is based on coincidence, that is, anyone who accidentally / incidentally meets with the researcher can be used as a sample. processing data using SPSS v21. Based on the results of the study, there are differences (perceptions) between the perceptions and expectations of the community on the dimensions of information quality, namely 96.25% and the quality of service interactions 96.66% while the dimensions of usability are considered good at 97.04%. The results of this study can be concluded that there is a difference (gap) between perceptions and expectations of the community on the dimensions of information quality and quality of service interactions while not on the dimensions of usability. Suggestions in this study were held a re-evaluation to see the quality dimension of information and the Serang City Education and Culture Office must prepare employees who specifically deal with this problem. Keywords: Service, Public, Education, Management, E-governance